Firefly at Stonybrook Farm - Pfeffer, Wendy 1929-; Mikec, Larry (Norwalk, Conn Soundprints, 2004)
Firefly emerges from the ground as an adult and explores the summer night sky, avoiding predators, being caught and released by a little girl, and finding a mate
"Smithsonian Institution."--Cover
2
Keywords: Fireflies -- Juvenile fiction; Fireflies -- Fiction